Peran Konselor untuk Membentuk Etika dan Estetika Siswa di Sekolah - Hasibuan, Ummi Kalsum (Guidance and Counseling Study Program, Pattimura University, 2023)
The purpose of this study is for counselors to know how to form the ethics and aesthetics of students at school. The essence of the counselor is always to provide advice or direction about student problems or complaints so that the ethics and aesthetics of students who have good morals are formed. The method used in this research is carried out using books, magazines, and journals that examine the role of counselors in schools. The results of this study are counselors who play a role in the formation of ethics and aesthetics for students at the Baitul Hikmah al-Zain Foundation participate in adding to existing activities at school such as the program to welcome students in the morning which will foster aesthetic value in students, making extracurricular activities this al- The Qur'an which values religion to form encourages students to have good ethics, and so on.